If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6-3z=-6
We move all terms to the left:
6-3z-(-6)=0
We add all the numbers together, and all the variables
-3z+12=0
We move all terms containing z to the left, all other terms to the right
-3z=-12
z=-12/-3
z=+4
| -8x=75-1x | | -6p-(p-1)=-4-8p | | 3x+2÷5=x÷3-1÷2 | | 2v+-4=0 | | -c+6=180 | | 11+-g=17 | | 16-2h=4 | | x/x+2=14/15 | | 11y-7.2=-19.3 | | 3(7x+4)=6(2x-1)-12 | | 5^(4x)=125 | | v+19/5=5 | | 5/35=g | | -10+h=4 | | Q+q+q+2q-4q=12 | | a^2+17a-3a-51=0 | | 35/5=g | | 4(j+11)=80 | | 45=9+9q | | 3c+4c-3c=8 | | 7x+(-3x)=-23 | | 11q-6q=5 | | 3(2l+2)+18=4(4l+3)−8 | | 3x-4/8=9 | | 12.5-m=9.7 | | y/7+66=73 | | 6y-5y=9 | | 7+2x5=-7-2/5 | | 2−–2r=–2 | | 3=3y-3 | | -90=-5(3b-6) | | 12=r/3+8 |